Classical and non-classical love triangles in prose V. Bryusov - Педченко, Елена Васильевна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2017)
The article describes the structure, motivation and interpretation of love triangles that represent forms of heroes relationship in V. Bryusov 's novel «The Fiery Angel» and the novel «The last pages of the diary of women». The characteristics of the love triangles are allocated that are conventionally presented as classical and non-classical, as well as their presence in the Russian literature of the XIX century. The game of reminiscence is traced by the author and heroes V. Bryusov correlation with heroes F. M. Dostoevsky («The Idiot» novel and the novel «The Eternal Husband») in the image of the triangular relationship.